Boron-nitrogen compound containing cycloalkyl spacer, blue light-emitting composition and organic electroluminescent device comprising same
By introducing boron nitrogen compounds with a cycloalkyl structure at the paraposition position of the phenyl group on the side of the boron nitrogen parent nucleus, the problems of the decrease in T1 value, the decrease in efficiency and the widening of the spectrum after the molecular orientation is improved in the prior art, and an organic electroluminescent device with high BI efficiency and long life is achieved.
Patent Information
- Application Number
- CN202411944962.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-04
AI Technical Summary
While improving molecular orientation, existing boron nitrogen blue light guest materials may reduce the T1 value, affecting the TADF process, leading to a decrease in efficiency, and there are problems of spectral widening and spectral redshift.
Using a boron nitrogen compound containing a cycloalkyl spacer, a cycloalkyl structure substituted or paralleled by an aryl group is introduced at the paraposition position of the phenyl group on the side of the boron nitrogen parent nucleus to expand the molecular size of the boron nitrogen parent nucleus plane direction, improve the molecular orientation, and avoid the efficiency reduction caused by aryl π-π interaction.
It significantly improves the BI efficiency of organic electroluminescent devices, avoids spectral widening and spectral redshift, and extends the operating life of the device.
Smart Images

Figure CN119751492A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of OLED, and specifically comprises a boron nitrogen compound containing a cycloalkyl spacer, a blue light-emitting composition and an organic electroluminescent device containing the same. Background Art
[0002] In recent years, optoelectronic devices based on organic materials have become increasingly popular. Examples of such organic optoelectronic devices include organic light-emitting diodes (OLEDs), organic field effect transistors, organic photovoltaic cells, organic sensors, etc. Among them, OLED has developed particularly rapidly and has achieved commercial success in the field of information display. OLED can provide highly saturated red, green, and blue colors. Full-color display devices made of OLED do not require additional backlight sources and have the advantages of brilliant colors, short response time, wide color gamut, and high contrast.
[0003] The coupling efficiency refers to the ratio of the light emitted by the luminescent molecules to the light output to the outside. Usually, after the isotropic molecules are formed into a thin film by thermal evaporation technology, each luminescent molecule has no definite directionality and exists in a disordered state, which causes the emitted light to be lost in the film layer, and the coupling efficiency is low, generally assumed to be 0.2. In order to improve the coupling efficiency of blue light materials, one of the more effective ways is to improve the molecular orientation of the guest material in the luminescent layer. In the currently disclosed boron nitrogen blue light guest materials, rigid aromatic groups such as biphenyl and terphenyl are usually attached to the boron nitrogen parent core to expand the molecular size of the boron nitrogen parent core in the plane direction, so as to improve its molecular orientation during film formation. This method can indeed improve the molecular orientation to a certain extent. However, with in-depth research, we found that directly connecting the long conjugated aromatic structure to the boron nitrogen parent core will reduce the T1 value of the guest material, which is not conducive to the TADF process of the guest material and causes a decrease in efficiency. When the host material selects anthracene structure substituted with aromatic groups, there is an obvious aromatic π-π interaction, which not only enhances the interaction between the guest material molecules and the host material molecules, but also increases the interaction between the guest material molecules. The strong interaction between the guest material molecules may cause the phenomenon of spectrum broadening and spectrum red shift after film formation, resulting in a further decrease in device efficiency. When the alkyl or cycloalkyl group is directly connected to the boron nitrogen parent core, the expansion of the molecular size is limited due to the free rotation of the single bond between the carbon atoms on the alkyl group, and the molecular orientation cannot be effectively improved. Therefore, it is urgent to develop new compounds that can expand the molecular size in the plane direction of the boron nitrogen parent core to improve the device efficiency, while preventing the undesirable phenomenon of spectrum broadening and spectrum red shift. Summary of the invention
[0004] In view of the above problems existing in the prior art, the present invention provides a boron nitrogen compound containing a cycloalkyl spacer, a blue light-emitting composition and an organic electroluminescent device containing the same.
[0005] In the present invention, the spacer refers to the Ar 1 ,Ar 2 A group that is directly connected to the phenyl group on the side of the boron nitrogen parent core.
[0006] To achieve the above objectives, the technical solutions adopted by the present invention include:
[0007] The first aspect of the present invention provides a boron nitrogen compound containing a cycloalkyl group, wherein the general structural formula of the boron nitrogen compound is as shown in Formula I:
[0008]
[0009] in,
[0010] X is selected from S or O;
[0011] R 1 , R 2 represents a single substituent to the maximum permissible substituent, each independently selected from any one or a combination of hydrogen, deuterium, a substituted or unsubstituted alkyl group having 1 to 30 carbon atoms, a substituted or unsubstituted cycloalkyl group having 3 to 30 carbon atoms, a substituted or unsubstituted aryl group having 6 to 60 carbon atoms, a substituted or unsubstituted carbazole group having 16 to 60 carbon atoms, and a substituted or unsubstituted arylamine group having 16 to 60 carbon atoms, and two or more of the R 1 , R 2 Can be fused to each other to form a ring;
[0012] R 3 represents a single substituent to the maximum permissible substituent, selected from one or more of hydrogen, deuterium, a substituted or unsubstituted alkyl group having 1 to 30 carbon atoms, a substituted or unsubstituted cycloalkyl group having 3 to 30 carbon atoms, a substituted or unsubstituted aryl group having 6 to 60 carbon atoms, a substituted or unsubstituted arylamine group, and a substituted or unsubstituted phenylsilyl group. When the R 3 When multiple substituents are represented, two or more adjacent R 3 Can bond to each other to form a ring;
[0013] Ar 1 ,Ar 2 represents a single substituent to the maximum permissible substituent, each independently selected from any one or a combination of substituted or unsubstituted alkyl having 1 to 30 carbon atoms, substituted or unsubstituted cycloalkyl having 3 to 30 carbon atoms, substituted or unsubstituted aryl having 6 to 60 carbon atoms, and substituted or unsubstituted heteroaryl having 5 to 60 carbon atoms. 1 ,Ar 2When multiple substituents are represented, two or more adjacent substituents may be bonded to each other to form a ring, and Ar 1 ,Ar 2 At least one of the following structures is selected:
[0014]
[0015] R 4 , R 5 Each is independently selected from one or more of a substituted or unsubstituted cycloalkyl group having 3 to 30 carbon atoms, a substituted or unsubstituted aryl group having 6 to 60 carbon atoms, a substituted or unsubstituted condensed ring aryl group having 5 to 60 carbon atoms, a substituted or unsubstituted dimethylfluorenyl group, and a substituted or unsubstituted tetramethyl-tetrahydronaphthyl group.
[0016] In formula I, any hydrogen can be replaced by deuterium, any nitrogen can be replaced by nitrogen-15, any sulfur can be replaced by sulfur-33, sulfur-34 or sulfur-36, any oxygen can be replaced by oxygen-17 or oxygen-18, any carbon can be replaced by carbon-13, and any boron can be replaced by boron-11.
[0017] Further, Ar 1 Selected from Any one of the above, wherein the boron nitrogen compound is selected from the general structure shown in Formula I-1:
[0018]
[0019] Further, Ar 2 Selected from Any one of the above, wherein the boron nitrogen compound is selected from the general structure shown in Formula I-2:
[0020]
[0021] Further, Ar 1 ,Ar 2 At least one of the structures shown below is selected from:
[0022]
[0023]
[0024] Furthermore, the R 1 , R 2Each is independently selected from one or more of hydrogen, deuterium, a substituted or unsubstituted alkyl group having 1 to 10 carbon atoms, a substituted or unsubstituted cycloalkyl group having 3 to 10 carbon atoms, a substituted or unsubstituted aryl group having 6 to 20 carbon atoms, a substituted or unsubstituted carbazolyl group having 16 to 30 carbon atoms, and a substituted or unsubstituted aromatic amine group having 16 to 30 carbon atoms.
[0025] Furthermore, the R 1 , R 2 Each independently selected from one or more of a tert-butyl group, a substituted or unsubstituted aromatic amine group having 16 to 30 carbon atoms, a carbazole group, and a cyclohexyl group; when the R 1 , R 2 When a substituent is present, the substituent is selected from one or more of methyl, ethyl, tert-butyl, cyclopentyl, cyclohexyl and phenyl.
[0026] Furthermore, the R 3 Any one or more selected from hydrogen, deuterium, a substituted or unsubstituted alkyl group having 1 to 10 carbon atoms, a substituted or unsubstituted cycloalkyl group having 3 to 10 carbon atoms, a substituted or unsubstituted aryl group having 6 to 20 carbon atoms, a substituted or unsubstituted arylamine group, and a substituted or unsubstituted phenylsilyl group.
[0027] Furthermore, the R 3 One or more selected from methyl, ethyl, tert-butyl, phenyl, phenylsilyl, cycloalkyl having 3 to 10 carbon atoms, alkyl substituted or unsubstituted aromatic amine having 6 to 20 carbon atoms.
[0028] Further, the boron nitrogen compound is selected from any one of the following structures:
[0029]
[0030]
[0031]
[0032]
[0033]
[0034]
[0035]
[0036]
[0037] A second aspect of the present invention provides a blue light-emitting composition, which comprises the boron nitrogen compound as described above and an anthracene compound having a general structural formula of Formula II;
[0038]
[0039] D stands for deuterium;
[0040] n represents 0 or 7, m represents 0 or 8, x represents 0 or 3, y represents 0 or 4, and n and m are not 0 at the same time, and x and y are not 0 at the same time.
[0041] In formula II, any hydrogen can be replaced by deuterium, any nitrogen can be replaced by nitrogen-15, any sulfur can be replaced by sulfur-33, sulfur-34 or sulfur-36, any oxygen can be replaced by oxygen-17 or oxygen-18, and any carbon can be replaced by carbon-13.
[0042] Furthermore, the anthracene compound represented by formula II is selected from one of the structures shown below:
[0043]
[0044] It should be noted that the above only provides the structures of some typical anthracene-based host materials by way of example. Technicians can understand that the improvement effect on improving the aromatic π-π interaction between the guest material molecules and the host material molecules, as well as the interaction between the guest material molecules, is also applicable to other typical anthracene-based host materials.
[0045] The third aspect of the present invention provides an organic electroluminescent device, which includes an anode, a hole transport region, a light-emitting layer, an electron transport region, and a cathode arranged in sequence on a substrate; wherein the light-emitting layer includes one or more boron nitrogen compounds as described above, wherein the light-emitting layer includes a host material and a guest material, and the guest material includes one or more boron nitrogen compounds with the structure described above.
[0046] The fourth aspect of the present invention provides an organic electroluminescent device, which includes an anode, a hole transport region, a light-emitting layer, an electron transport region, and a cathode arranged in sequence on a substrate; wherein the light-emitting layer contains the blue light-emitting composition as described above.
[0047] Beneficial effects of the present invention:
[0048] The present invention provides a boron nitrogen compound containing a cycloalkyl spacer, wherein the phenyl group at the side of the boron nitrogen parent nucleus is located at the para position, that is, Ar 1 or Ar 2The introduction of a cycloalkyl structure substituted by an aromatic group or in parallel, or substituted by a cycloalkyl group, can not only expand the size of the boron nitrogen parent core plane direction, so that the material has a better molecular orientation when forming a film, but also maintain the good linearity or planarity of the boron nitrogen guest material. Specifically: after the introduction of a cycloalkyl structure substituted by an aromatic group or in parallel into the boron nitrogen parent core structure, since the aromatic group on the cycloalkyl group is not directly connected to the parent core, the structure can interrupt the conjugation and cut off the direct connection between the parent core and the low T1 fragment on the basis of ensuring that its own structure is linear and expanding the size in one direction, thereby avoiding the influence of the π-π interaction of the substituted aromatic group on the parent core, thereby avoiding the spectral broadening and spectral red shift caused by the strong interaction between the guest material molecules, and also reducing the concentration quenching caused by the aggregation of the guest material due to the strong interaction force, thereby improving the BI efficiency of the device; and the introduction of a cycloalkyl structure substituted by a cycloalkyl group at a specific site can also increase the size of the molecular structure during the twisting process of the flexible skeleton, increase the probability of the molecules being arranged in a horizontal orientation, and reduce the interaction between the guest material molecules to a greater extent, thereby improving the device efficiency. Therefore, when the boron nitrogen compound containing a cycloalkyl spacer provided by the present invention is used as a guest material of the light-emitting layer to prepare an organic electroluminescent device, the BI efficiency of the organic electroluminescent device can be significantly improved and the working life of the device can be extended to a certain extent. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 It is a schematic structural diagram of the organic electroluminescent device of the present invention.
[0050] Description of the drawings: 1-substrate, 2-anode, 3-hole injection layer, 4-hole transport layer, 5-luminescence auxiliary layer, 6-luminescent layer, 7-hole blocking layer, 8-electron transport layer, 9-electron injection layer, 10-cathode. DETAILED DESCRIPTION
[0051] In order to more clearly understand the content of the present invention, it will be described in detail with reference to the drawings and embodiments.
[0052] The compounds of the present invention are suitable for use in light-emitting elements, display panels and electronic devices, and are particularly suitable for use in organic electroluminescent devices. The electronic device described in the present invention is a device comprising a layer of at least one organic compound, and the device may also comprise an inorganic material or a layer formed entirely of an inorganic material. The electronic device is preferably an organic electroluminescent device (OLED), an organic integrated circuit (O-IC), an organic field effect transistor (O-FET), an organic thin film transistor (O-TFT), an organic light-emitting transistor (O-LET), an organic solar cell (O-SC), an organic dye-sensitized solar cell (O-DSSC), an organic optical detector, an organic photoreceptor, an organic field quenching device (O-FQD), a light-emitting electrochemical cell (LEC), an organic laser diode (O-laser) and an organic plasma emission device. The electronic device is preferably an organic electroluminescent device (OLED). The structural schematic diagram of an exemplary organic electroluminescent device is shown in FIG. Figure 1 shown.
[0053] Experimental Section
[0054] In order to understand the content of the present invention more clearly, the polycyclic compound, the preparation method of the compound and the luminescent characteristics of the device will be explained in detail in conjunction with the examples. Various chemical reactions can be applied to the synthetic method of the compound of an embodiment of the present invention. However, it should be noted that the synthetic method of the compound of an embodiment of the present invention is not limited to the synthetic method described below. Unless otherwise indicated, the subsequent synthesis is carried out in anhydrous solvent under a protective gas atmosphere. Solvents and reagents can be purchased from conventional reagent suppliers.
[0055] Intermediate synthesis
[0056] Synthesis route of bromine-containing intermediates:
[0057]
[0058] The synthesis of A01 is described in detail below.
[0059]
[0060] Y01 (3.73 g, 0.025 mol), Q01 (6.19 g, 0.023 mol) and sodium tert-butoxide (2.64 g, 0.03 mol) were added to toluene (200 mL), and then bis(dibenzylideneacetonepalladium) (0.23 g, 0.25 mmol) and SPhos (0.21 g, 0.5 mmol) were introduced under nitrogen protection. The reaction system was then heated to 110° C., refluxed and maintained for 8 hours, cooled to room temperature, quenched with water and separated, the organic phase was filtered and dried over anhydrous sodium sulfate, the solvent was removed by rotation, and the crude product was purified by column chromatography to obtain product S01: 5.36 g, yield: 69%, MS (m / z) (M+): 338.
[0061] S01 (8.45 g, 0.025 mol), T01 (5.70 g, 0.023 mol) and sodium tert-butoxide (2.64 g, 0.03 mol) were added to toluene (200 mL), and then bis(dibenzylideneacetonepalladium) (0.23 g, 0.25 mmol) and SPhos (0.21 g, 0.5 mmol) were introduced under nitrogen protection. The reaction system was then heated to 110°C, refluxed and maintained for 8 hours, cooled to room temperature, quenched with water and separated, the organic phase was filtered and dried over anhydrous sodium sulfate, the solvent was removed by rotation, and the crude product was purified by column chromatography to obtain product U01: 8.81 g, yield: 76%, MS (m / z) (M+): 504.
[0062] U01 (25.2 g, 0.05 mol), V01 (10.94 g, 0.045 mol) and sodium tert-butoxide (5.28 g, 0.055 mol) were added to toluene (200 mL), and then bis(dibenzylideneacetonepalladium) (0.46 g, 0.50 mmol) and tri-tert-butylphosphine (0.26 g, 1 mmol) were introduced under nitrogen protection. The reaction system was then heated to 110° C., refluxed and maintained for 8 hours, cooled to room temperature, quenched with water and separated, the organic phase was filtered and dried over anhydrous sodium sulfate, the solvent was removed by rotation, and the crude product was purified by column chromatography to obtain product W01: 24.00 g, yield: 75%, MS (m / z) (M+): 711.
[0063] X01 (8.48 g, 0.025 mol), W01 (16.35 g, 0.023 mol) and sodium tert-butoxide (2.64 g, 0.03 mol) were added to toluene (200 mL), and then bis(dibenzylideneacetonepalladium) (0.23 g, 0.25 mmol) and SPhos (0.21 g, 0.5 mmol) were introduced under nitrogen protection. The reaction system was then heated to 110° C., refluxed and maintained for 8 hours, cooled to room temperature, quenched with water and separated, the organic phase was filtered and dried over anhydrous sodium sulfate, the solvent was removed by rotation, and the crude product was purified by column chromatography to obtain product A01: 10.60 g, yield: 50%, MS (m / z) (M+): 809.
[0064] After A01 is obtained through the above process, intermediates A02, A10, A11, A12, A13, A14, A15, A16 and A17 can be easily obtained using a method similar to A01.
[0065] Synthesis route of chlorine-containing intermediates:
[0066]
[0067] The synthesis of A03 is described in detail below.
[0068]
[0069] S03 (9.95 g, 0.025 mol), T03 (7.06 g, 0.023 mol) and sodium tert-butoxide (2.64 g, 0.03 mol) were added to toluene (200 mL), and then bis(dibenzylideneacetonepalladium) (0.23 g, 0.25 mmol) and SPhos (0.21 g, 0.5 mmol) were introduced under nitrogen protection. The reaction system was then heated to 110°C, refluxed and maintained for 8 hours, cooled to room temperature, quenched with water and separated, the organic phase was filtered and dried over anhydrous sodium sulfate, the solvent was removed by rotation, and the crude product was purified by column chromatography to obtain product U03: 10.89 g, yield: 76%, MS (m / z) (M+): 623.
[0070] U03 (31.2 g, 0.05 mol), V03 (6.71 g, 0.045 mol) and sodium tert-butoxide (5.28 g, 0.055 mol) were added to toluene (200 mL), and then bis(dibenzylideneacetonepalladium) (0.46 g, 0.50 mmol) and tri-tert-butylphosphine (0.26 g, 1 mmol) were introduced under nitrogen protection. The reaction system was then heated to 110°C, refluxed and maintained for 8 hours, cooled to room temperature, quenched with water and separated, the organic phase was filtered and dried over anhydrous sodium sulfate, the solvent was removed by rotation, and the crude product was purified by column chromatography to obtain product W03: 26.16 g, yield: 79%, MS (m / z) (M+): 736.
[0071] X03 (8.10 g, 0.025 mol), W03 (16.93 g, 0.023 mol) and sodium tert-butoxide (2.64 g, 0.03 mol) were added to toluene (200 mL), and then bis(dibenzylideneacetonepalladium) (0.23 g, 0.25 mmol) and SPhos (0.21 g, 0.5 mmol) were introduced under nitrogen protection. The reaction system was then heated to 110° C., refluxed and maintained for 8 hours, cooled to room temperature, quenched with water and separated, the organic phase was filtered and dried over anhydrous sodium sulfate, the solvent was removed by rotation, and the crude product was purified by column chromatography to obtain product A03: 14.64 g, yield: 65%, MS (m / z) (M+): 979.
[0072] After A03 is obtained through the above process, intermediates A04, A05, A06, A07, A08, A09, A18, A19 and A20 can be easily obtained using a method similar to A03.
[0073] Compound synthesis
[0074] Compound Synthesis Example 1
[0075]
[0076] A01 (9.22 g; 10 mmol) was added to tert-butylbenzene (125 ml), then the temperature was lowered to -50°C under nitrogen protection, 12.4 ml (21 mmol) of 1.7 M n-butyl lithium pentane solution was added, the temperature was raised to 60°C and stirred for 2 hours, then the temperature was lowered to 0°C, 2.0 ml (21 mmol) of boron tribromide was added and stirred for 0.5 h, the temperature was lowered to 0°C, 3.65 ml (21 mmol) of N, N-diisopropylethylamine was added, the temperature was raised to 60°C and stirred for 2 h, the temperature was lowered to room temperature, ice water was added to quench and separate the liquids, the organic phase was filtered and dehydrated with anhydrous magnesium sulfate, the organic solvent was removed by rotation, and the crude product was purified by recrystallization from dichloromethane and n-heptane. Finally, the product B01: 0.94 g, yield: 11%, MS (m / z) (M+): 852 was obtained.
[0077] Compound Synthesis Example 2
[0078]
[0079] The method is the same as that of Synthesis Example 1, except that A02 (10.24 g; 10 mmol) is used to replace A01, and the final product B02 is 0.67 g, with a yield of 7%, and MS (m / z) (M+): 954.
[0080] Compound Synthesis Example 3
[0081]
[0082] A03 (9.80 g; 10 mmol) was added to tert-butylbenzene (125 ml), then the temperature was lowered to -50 ° C under nitrogen protection, 12.4 ml (21 mmol) of 1.7 M tert-butyl lithium pentane solution was added, the temperature was raised to 60 ° C and stirred for 2 hours, then the temperature was lowered to 0 ° C, 2.0 ml (21 mmol) of boron tribromide was added and stirred for 0.5 h, the temperature was lowered to 0 ° C, 3.65 ml (21 mmol) of N, N-diisopropylethylamine was added, the temperature was raised to 60 ° C and stirred for 2 h, and ice water was added to cool to room temperature to quench and separate the liquids. After filtering the organic phase, anhydrous magnesium sulfate was used to remove water, and after the organic solvent was removed, the crude product was purified by recrystallization from dichloromethane and n-heptane. Finally, the product B03: 0.86 g, yield: 9%, MS (m / z) (M+): 953 was obtained.
[0083] Compound Synthesis Example 4
[0084]
[0085] The method is the same as that of Synthesis Example 3, except that A04 (10.22 g; 10 mmol) is used to replace A03, and finally the product B04 is obtained: 0.9 g, yield: 9%, MS (m / z) (M+): 996.
[0086] Compound Synthesis Example 5
[0087]
[0088] The method is the same as that of Synthesis Example 3, except that A05 (14.27 g; 10 mmol) is used to replace A03, and the final product B05 is 0.94 g, with a yield of 9%, MS (m / z) (M+): 1041.
[0089] Compound Synthesis Example 6
[0090]
[0091] The method is the same as that of Synthesis Example 3, except that A06 (11.57 g; 10 mmol) is used to replace A03, and finally the product B06 is obtained: 1.36 g, yield: 12%, MS (m / z) (M+): 1131.
[0092] Compound Synthesis Example 7
[0093]
[0094] The method is the same as that of Synthesis Example 3, except that A07 (12.93 g; 10 mmol) is used to replace A03, and the final product B07 is 1.39 g, with a yield of 11%, and MS (m / z) (M+): 1267.
[0095] Compound Synthesis Example 8
[0096]
[0097] The method is the same as that of Synthesis Example 3, except that A08 (11.61 g; 10 mmol) is used to replace A03, and the final product B08 is 1.02 g, with a yield of 9%, and MS (m / z) (M+): 1135.
[0098] Compound Synthesis Example 9
[0099]
[0100] The method is the same as that of Synthesis Example 3, except that A09 (12.61 g; 10 mmol) is used to replace A03, and the final product B09 is 0.74 g, with a yield of 6%, and MS (m / z) (M+): 1235.
[0101] Compound Synthesis Example 10
[0102]
[0103] The method is the same as that of Synthesis Example 1, except that A10 (13.09 g; 10 mmol) is used to replace A01, and finally product B10 is obtained: 0.74 g, yield: 6%, MS (m / z) (M+): 1238.
[0104] Compound Synthesis Example 11
[0105]
[0106] The method is the same as that of Synthesis Example 1, except that A11 (9.9 g; 10 mmol) replaces A01, and finally the product B11 is obtained: 0.74 g, yield: 8%, MS (m / z) (M+): 919.
[0107] Compound Synthesis Example 12
[0108]
[0109] The method is the same as that of Synthesis Example 1, except that A12 (11.3 g; 10 mmol) replaces A01, and finally the product B12 is obtained: 1.17 g, yield: 11%, MS (m / z) (M+): 1060.
[0110] Compound Synthesis Example 13
[0111]
[0112] The method is the same as that of Synthesis Example 1, except that A13 (11.79 g; 10 mmol) replaces A01, and finally the product B13 is obtained: 1.11 g, yield: 10%, MS (m / z) (M+): 1108.
[0113] Compound Synthesis Example 14
[0114]
[0115] The method is the same as that of Synthesis Example 1, except that A14 (10.74 g; 10 mmol) replaces A01, and finally the product B14 is obtained: 0.5 g, yield: 5%, MS (m / z) (M+): 1004.
[0116] Compound Synthesis Example 15
[0117]
[0118] The method is the same as that of Synthesis Example 1, except that A15 (13.37 g; 10 mmol) replaces A01, and finally the product B15 is obtained: 0.76 g, yield: 6%, MS (m / z) (M+): 1266.
[0119] Compound Synthesis Example 16
[0120]
[0121] The method is the same as that of Synthesis Example 1, except that A16 (12.05 g; 10 mmol) replaces A01, and finally the product B16 is obtained: 0.91 g, yield: 8%, MS (m / z) (M+): 1134.
[0122] Compound Synthesis Example 17
[0123]
[0124] The method is the same as that of Synthesis Example 1, except that A17 (12.87 g; 10 mmol) replaces A01, and finally the product B17 is obtained: 1.46 g, yield: 12%, MS (m / z) (M+): 1216.
[0125] Compound Synthesis Example 18
[0126]
[0127] The method is the same as that of Synthesis Example 3, except that A18 (13.36 g; 10 mmol) is used to replace A03, and the final product B18 is 0.66 g, with a yield of 5%, MS (m / z) (M+): 1310.
[0128] Compound Synthesis Example 19
[0129]
[0130] The method is the same as that of Synthesis Example 3, except that A19 (13.02 g; 10 mmol) replaces A03, and finally the product B19 is obtained: 1.02 g, yield: 8%, MS (m / z) (M+): 1276.
[0131] Compound Synthesis Example 20
[0132]
[0133] The method is the same as that of Synthesis Example 3, except that A20 (13.72 g; 10 mmol) is used to replace A03, and the final product B20 is 1.62 g, with a yield of 12%, MS (m / z) (M+): 1346.
[0134] Comparative Example Compound
[0135] Some typical guest material structures that have been tried during the research are summarized as follows:
[0136]
[0137] Some typical main material structures that have been tried during the research are summarized as follows:
[0138]
[0139] Compound properties
[0140] In order to explore the reasons why the synthetic example compounds of the present invention show efficiency advantages over the comparative example compounds in the device, the half-width, spectral peak value, and molecular level orientation of the synthetic example compounds of the present invention and the comparative example compounds were tested to help illustrate that although the structural differences between the compounds of the present invention and the comparative example compounds are relatively small, there are still significant performance differences.
[0141] Half-peak width test method: The composition shown in Table 1 is formed into a film on a high-transmittance quartz glass sheet by dual-source co-evaporation, wherein the guest material doping mass concentration is 1%, the host material mass concentration ratio is 99%, and the film thickness is 60nm. The Horiba Fluorolog-3 series fluorescence spectrometer is used for testing. The luminescence intensity in the range of 400-620nm is tested. After the luminescence intensity is normalized, the spectral peak width corresponding to the intensity value of 0.5 is the FWHM. The results are shown in Table 1.
[0142] It should be noted that the narrower the spectral half-width (FWHM), the smaller the influence of the π-π interaction of the substituent aromatic group on the parent core after the material is evaporated into a film, thereby avoiding the spectrum broadening and spectral red shift caused by excessive interaction between the guest material molecules, reducing the concentration quenching of the guest material caused by excessive interaction, and improving the BI efficiency. In addition, the narrow spectral half-width means that its luminescence in the non-blue spectral region is weak, and the color purity of the material luminescence is better.
[0143] The transition dipole moment orientation of the molecules in the light-emitting layer was measured by angle-dependent fluorescence spectroscopy, using a molecular orientation test system produced by Hamamatsu (HAMAMATSU) of Japan. Test method: The composition shown in Table 1 was co-evaporated on a high-transmittance quartz glass sheet to form an organic film, wherein the guest material doping mass concentration ratio was 3%, and the host material mass concentration ratio was 97%. Then, the sample to be tested was excited with 365nm ultraviolet light, so that the sample to be tested emitted light, and the p-polarized light in the emitted light was detected by the polarizer and received by the detector, and the distribution of the fluorescence intensity of the organic film with the test angle was measured, and its anisotropy factor Θ (dimensionless) was determined by optical fitting software;
[0144]
[0145] In the formula, p z represents the vertical dipole electrode moment, p represents the dipole electrode moment, It represents the emission power of the total vertical dipoles, Σp2 represents the total emission power of all dipoles. The smaller Θ is, the higher the probability that the molecules are arranged in a horizontal orientation, which means that the material has a better molecular orientation. It also indicates that the more horizontal luminescent components there are in the organic film guest material, the higher the utilization rate of the guest material's radiant luminescence.
[0146] The specific results are shown in Table 1.
[0147] Table 1
[0148]
[0149]
[0150] It can be seen from the above test results that the composition provided by the present invention has a narrower half-peak width and a smaller anisotropy factor θ than the comparative example, indicating that the boron nitrogen compound containing a cycloalkyl spacer provided by the present invention is provided by Ar 1 and Ar 2 The specific substituted cycloalkyl structure at the position can improve the molecular orientation without increasing the half-peak width. The narrower half-peak width and larger molecular orientation mean greater efficiency advantages in top-emitting devices.
[0151] Specifically, compared with B06, DBBD01, the compound provided by the present invention can expand the molecular size by adding a benzene ring after the cycloalkyl group, thereby significantly improving the molecular orientation; compared with the single cyclopentyl group, DBBD02, the compound provided by the present invention can further expand the molecular size by further connecting the cyclopentyl group to the cyclohexyl group, thereby significantly improving the molecular orientation; compared with B03, DBBD03, the compound provided by the present invention has a phenyl group on the cyclopentyl group, and the cyclopentyl phenyl group can avoid conjugation extension and significantly reduce the half peak width; DBBD04 Compared with B04, the compound B04 provided by the present invention has a phenyl group on the cyclohexyl group, and the cyclohexyl phenyl group can avoid conjugation extension and significantly reduce the half-peak width; compared with DBBD05 and B06, since the comparative compound lacks a cyclohexyl group as a spacer group, although it has a relatively good molecular orientation, its half-peak width is also significantly increased, indicating that since the long conjugated segment is directly connected to the parent nucleus, the excited state energy level of the parent nucleus is reduced, and multiple aromatic groups directly connected to the parent nucleus mean that the π-π interaction is strong, which means that the luminescence of the material is likely to be red-shifted, which is not conducive to improving the efficiency of the device.
[0152] The composition composed of the preferred BH and BD of the present invention is adopted. Since the anthracene core skeleton of the BH of the present invention has a naphthalene structure with small polarity on one side and a dibenzofuran structure with large polarity on the other side, this structure makes it easy for the main body to present a horizontal orientation in the stacking arrangement. Dibenzofuran makes the main body itself have a larger polarity than the comparative main body, and it is easy to interact with BD, and the luminescence spectrum will not be broadened or the orientation will be worse.
[0153] Fabrication and characterization of OLEDs
[0154] Device Embodiment
[0155] The organic electroluminescent device provided by the present invention comprises an anode, a hole transport region, a light-emitting layer, an electron transport region, and a cathode which are sequentially arranged on a substrate;
[0156] Furthermore, the hole transport region includes a hole injection layer, a hole transport layer and a light-emitting auxiliary layer; and the electron transport region includes an electron transport layer and an electron injection layer.
[0157] Furthermore, the light-emitting layer is composed of a host material and a guest material, and the guest material of the light-emitting layer can be composed of one or more of the above-mentioned molecular materials.
[0158] The anode in the embodiment adopts anode materials commonly used in the art, such as ITO, Ag or their multilayer structures. The hole injection layer adopts hole injection materials commonly used in the art, and F4TCNQ, HATCN, NDP-9, etc. are added for doping. The hole transport layer adopts hole transport materials commonly used in the art. The light-emitting layer adopts the host and guest material composition provided by the present invention. The electron transport layer adopts electron transport materials commonly used in the art. The electron injection layer adopts electron injection materials commonly used in the art, such as LiQ, LiF, Yb, etc. The cathode adopts materials commonly used in the art, such as metal Al, Ag or metal mixtures (Ag-doped Mg, Ag-doped Ca, etc.).
[0159] The electrode preparation method and the deposition method of each functional layer in this embodiment are conventional methods in the art, such as vacuum thermal evaporation or inkjet printing, etc., which will not be described in detail here. Only some process details and test methods in the preparation process are supplemented as follows:
[0160] Device Example 1
[0161] The substrates used in the present invention were subjected to the following operations: the ITO substrate was patterned so that its luminous area had a size of 3 mm×3 mm, and then water / isopropanol ultrasound, UV / ozone irradiation, and then dried at 100°C. After that, the ITO substrate was mounted on a substrate holder of a vacuum deposition device and the pressure was adjusted so that the vacuum rate became 1×10 -7torr. Then the following operations were performed: first, on the ITO layer (anode) formed on the substrate, compound HT01 and compound PD01 (the mass ratio of HT01 to PD01 was 97:3) were vacuum deposited with a thickness of 10 nm to form a hole injection layer; secondly, on the hole injection layer, compound HT01 was vacuum deposited with a thickness of 120 nm to form a hole transport layer; secondly, on the hole transport layer, compound BP01 was vacuum deposited with a thickness of 5 nm to form an electron blocking layer; secondly, on the electron blocking layer, a mixture of compound BH01 provided by the present invention and compound B01 was vacuum deposited with a thickness of 20 nm to form a light-emitting layer, wherein BH01 was used as a host material and B01 was used as a guest material, and the mass ratio of the host material to the guest material was 98:2; then, on the light-emitting layer, compound HB01 was vacuum deposited with a thickness of 5 nm to form a hole blocking layer; then Then, on the hole blocking layer, compound ET01 and compound LiQ (the mass ratio of ET01 to LiQ is 1:1) are vacuum deposited with a thickness of 20 nm to form an electron transport layer; then, on the electron transport layer, Yb is vacuum deposited with a thickness of 1 nm to form an electron injection layer, and then on the electron injection layer, Mg and Ag (the mass ratio of Mg and Ag is 1:9) are deposited with a thickness of 15 nm to form a cathode, and then on the cathode, compound CP01 is deposited with a thickness of 50 nm to form a covering layer. Finally, the vapor-deposited substrate is packaged, and the cleaned cover plate is coated with UV glue using a glue coating equipment, and then the coated cover plate is moved to the pressing section, and the vapor-deposited substrate is placed on the upper end of the cover plate. Finally, the substrate and the cover plate are bonded under the action of a bonding device, and the UV glue is light-cured to prepare a laminated organic electroluminescent device.
[0162] Except for the guest material of the light-emitting layer, the molecular structures of the materials in the remaining layers are as follows:
[0163]
[0164] Device Examples 2-20
[0165] The above method was used to prepare organic electroluminescent devices from the compounds described in other examples in Table 2, and the guest materials shown in the examples in Table 2 were used to replace B01 in device example 1 to prepare blue light organic electroluminescent device examples 2-20.
[0166] Device Comparison Examples 1-5
[0167] The above method was used to prepare organic electroluminescent devices from the compounds described in the comparative examples in Table 2, and the guest materials shown in the comparative examples in Table 2 were used to replace B01 in device example 1 to prepare blue light organic electroluminescent device comparative examples 1-5.
[0168] The OLED devices described above were tested by standard methods. For this purpose, at J = 10 mA / cm 2 The driving voltage and luminous efficiency of the organic electroluminescent device are determined at a current density of J = 10 mA / cm 2 When working under this condition, the luminous brightness drops to its initial value L after time LT95 0 95% of.
[0169] The test instruments and methods for testing the performance of the OLED devices in the above embodiments and comparative examples are as follows:
[0170] The luminous efficiency CE (cd / A) and color coordinates (CIEy) were tested using a spectrum scanner PhotoResearch PR-635;
[0171] Current density and lighting voltage: tested using a digital source meter Keithley 2400;
[0172] The luminous efficiency of blue light devices is greatly affected by chromaticity. The industry generally uses BI value as the basis for the efficiency of blue light devices. BI (Blue index) is obtained by dividing the luminous efficiency CE (cd / A) by the color coordinate (CIEy);
[0173] Life test: Use silicon photoelectric OLED device life test system.
[0174] The performance test results of the above devices are listed in Table 2.
[0175] Table 2 Blue light device performance test results
[0176]
[0177] It can be seen from the above results that compared with the comparative example compounds and the prepared device comparative examples, under similar mother core skeletons, the compounds provided by the present invention can significantly improve the BI efficiency of top emission devices. After the characteristic fragments that greatly increase the size of the mother core plane direction are introduced into the compounds provided by the present invention, these rod-shaped large-size characteristic fragments are connected to the boron nitrogen mother core by using a cycloalkyl structure, and the conjugation of the aromatic substituents can be blocked while the size is expanded, thereby avoiding the widening of the half-peak width caused by the enhanced intermolecular effect due to the substantial extension of the conjugation, thereby having a better molecular orientation, and ultimately having a significant advantage in the BI efficiency in the top emission device; and the device embodiment constructed by the composition provided by the present invention also shows a certain lifespan advantage, which may be due to the good interaction between the host and the guest, and the spacing effect of the cycloalkyl structure on the BD material, especially compared with DBBD05 without a cycloalkyl spacer, the spacer of the present invention may play a certain role in avoiding the intermolecular aggregation quenching caused by the peripheral aromatic group, and thus the lifespan is also slightly improved.
[0178] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.
Claims
1. A boron nitrogen compound containing a cycloalkyl spacer, characterized in that: The general structural formula of the boron nitrogen compound is shown in Formula I: in, X is selected from S or O; R1 and R2 represent a single substituent to the maximum permissible substituent, and are independently selected from any one or a combination of hydrogen, deuterium, a substituted or unsubstituted alkyl group having 1 to 30 carbon atoms, a substituted or unsubstituted cycloalkyl group having 3 to 30 carbon atoms, a substituted or unsubstituted aryl group having 6 to 60 carbon atoms, a substituted or unsubstituted carbazole group having 16 to 60 carbon atoms, and a substituted or unsubstituted arylamine group having 16 to 60 carbon atoms, and two or more of the R1 and R2 may be fused to form a ring; R3 represents a single substituent to the maximum permissible substituent, selected from one or more of hydrogen, deuterium, a substituted or unsubstituted alkyl group having 1 to 30 carbon atoms, a substituted or unsubstituted cycloalkyl group having 3 to 30 carbon atoms, a substituted or unsubstituted aryl group having 6 to 60 carbon atoms, a substituted or unsubstituted arylamine group, and a substituted or unsubstituted phenylsilyl group. When the R3 represents multiple substituents, two or more adjacent R3 groups may be bonded to each other to form a ring. Ar1 and Ar2 represent a single substituent to the maximum permissible substituent, and are independently selected from any one or a combination of substituted or unsubstituted alkyl groups having 1 to 30 carbon atoms, substituted or unsubstituted cycloalkyl groups having 3 to 30 carbon atoms, substituted or unsubstituted aryl groups having 6 to 60 carbon atoms, and substituted or unsubstituted heteroaryl groups having 5 to 60 carbon atoms. When Ar1 and Ar2 represent multiple substituents, two or more adjacent substituents may be bonded to each other to form a ring, and at least one of Ar1 and Ar2 is selected from the following structure: R4 and R5 are each independently selected from one or more of a substituted or unsubstituted cycloalkyl group having 3 to 30 carbon atoms, a substituted or unsubstituted aryl group having 6 to 60 carbon atoms, a substituted or unsubstituted condensed ring aryl group having 5 to 60 carbon atoms, a substituted or unsubstituted dimethylfluorenyl group, and a substituted or unsubstituted tetramethyl-tetrahydronaphthyl group.
2. The boron nitrogen compound according to claim 1, characterized in that Ar1 is selected from Any of the following; The boron nitrogen compound is selected from the general structure shown in Formula I-1: or Ar2 is selected from Any of the following; The boron nitrogen compound is selected from the general structure shown in Formula I-2:
3. The boron nitrogen compound according to claim 1, characterized in that At least one of Ar1 and Ar2 is selected from the following structures:
4. The boron nitrogen compound according to claim 1, characterized in that The R1 and R2 are each independently selected from one or more of hydrogen, deuterium, a substituted or unsubstituted alkyl group having 1 to 10 carbon atoms, a substituted or unsubstituted cycloalkyl group having 3 to 10 carbon atoms, a substituted or unsubstituted aryl group having 6 to 20 carbon atoms, a substituted or unsubstituted carbazole group having 16 to 30 carbon atoms, and a substituted or unsubstituted arylamine group having 16 to 30 carbon atoms; The R3 is selected from any one or more of hydrogen, deuterium, a substituted or unsubstituted alkyl group having 1 to 10 carbon atoms, a substituted or unsubstituted cycloalkyl group having 3 to 10 carbon atoms, a substituted or unsubstituted aryl group having 6 to 20 carbon atoms, a substituted or unsubstituted aromatic amino group, and a substituted or unsubstituted phenylsilyl group.
5. The boron nitrogen compound according to claim 1, characterized in that The R1 and R2 are each independently selected from one or more of a tert-butyl group, a substituted or unsubstituted aromatic amine group having 16 to 30 carbon atoms, a carbazole group, and a cyclohexyl group; when the R1 and R2 have a substituent, the substituent is selected from one or more of a methyl group, an ethyl group, a tert-butyl group, a cyclopentyl group, a cyclohexyl group, and a phenyl group; The R3 is selected from one or more of a methyl group, an ethyl group, a tert-butyl group, a phenyl group, a phenylsilyl group, a cycloalkyl group having 3 to 10 carbon atoms, and an alkyl group having 6 to 20 carbon atoms, substituted or unsubstituted aromatic amine group.
6. The boron nitrogen compound according to claim 1, characterized in that The boron nitrogen compound is selected from any one of the following structures:
7. A blue light-emitting composition, characterized in that: The blue light-emitting composition comprises the boron nitrogen compound according to any one of claims 1 to 6 and an anthracene compound having a general structural formula as shown in Formula II; D stands for deuterium; n represents 0 or 7, m represents 0 or 8, x represents 0 or 3, y represents 0 or 4, and n and m are not 0 at the same time, and x and y are not 0 at the same time.
8. The blue light-emitting composition according to claim 7, characterized in that: The anthracene compound represented by formula II is selected from one of the structures shown below:
9. An organic electroluminescent device, characterized in that: It includes an anode, a hole transport region, a light-emitting layer, an electron transport region, and a cathode which are sequentially arranged on a substrate; wherein the light-emitting layer includes a host material and a guest material, and the guest material includes one or more boron nitrogen compounds as described in any one of claims 1 to 6.
10. An organic electroluminescent device, characterized in that: It comprises an anode, a hole transport region, a light-emitting layer, an electron transport region, and a cathode which are sequentially arranged on a substrate; wherein the light-emitting layer contains the blue light-emitting composition according to claim 7 or 8.
Citation Information
Cited By
Polycyclic compound containing triphenyl silicon and polyalkyl substituent and organic electroluminescent device containing polycyclic compound
CN120865273A
A polycyclic compound containing triphenylsilicon and polyalkyl substituents and an organic electroluminescence device comprising the same
CN120865273B
A light-emitting material having excellent intrinsic thermal stability and an organic electroluminescent device comprising the same
CN122685641A